Cálculo de constantes ópticas de películas delgadas de Cu3BiS3 a través del método de Wolfe - Mesa, F.; Unidad de Estudios Universitarios, Universidad del Rosario, Bogotá-Colombia (2014)
Using the Wolfe method, we calculated the procurement of optical constants. These constants, absorption coefficient (α), refraction index of (n) and thin film thickness (d ), are significant in the optical characterization of the material. We compared the Wolfe method with the method employed by R. Swanepoel. To estimate the optical constants of semiconductor thin films, we developed a constrained nonlinear programming model, based solely, on known transmission data. Ultimately, we presented a solution to this nonlinear programming model for quadratic programming. Through numerical experiments and transmittance spectral data of Cu3BiS3 thin films, we obtained values of a= 10378.34 cm−1, n = 2.4595, d =989.71 nm and Eg= 1.39 Ev, demonstrating the reliability of the proposed method.